The influence of occupational health and safety signs on safe behavior among oil palm factory workers at PT. Sewangi Sawit Sejahtera - Sumarni, Rani; Santoso, Santoso; Hamid, Abdurrahman (Institute of Computer Science (IOCS), 2024)
The installation of safety signs in the palm oil factory of PT. Sewangi Sawit Sejahtera is still insufficiently attended to by the workers, as evidenced by the presence of several outdated safety signs that are no longer clearly visible, rendering the conveyed messages unclear. The general objective of this study is to determine the Influence of Safety Signs on Workers' Safety Behavior at the Palm Oil Factory of PT. Sewangi Sawit Sejahtera in 2021. The significance of this research lies in its role as a platform for exchanging information and providing education on workplace accident prevention. This study adopts a Quasi-Experimental Non-Randomized Control Group Pretest and Posttest Design, involving 40 workers in the factory. The research was conducted between August and September 2021. The findings indicate a significant impact on workers' safety behavior before and after the intervention in the Experimental group, as evidenced by the significance level of the paired t-test. Logistic Regression analysis reveals that the most influential variable on safety behavior is the presence of safety signs, followed by tenure, supervision, and age. Therefore, it is recommended that efforts be made to enhance socialization activities and training to improve workers' knowledge regarding workplace safety and health, along with repairing or replacing unclear or damaged safety signs within the company premises.